Re-examining a model for measuring Facebook interaction and relationship quality. Issue 3 (8th July 2019) - Achen, Rebecca M.
Abstract : Purpose: Research in sport has examined the use of social media by organizations and athletes, but little research has assessed the effectiveness of social media marketing, especially in terms of relationship-building. When relationship marketing is used as a framework for using social media, it should also be used to guide assessment. The purpose of this paper is to re-examine a model for measuring the impact of fans' Facebook interactions with their favorite sport team on relationship quality, purchase intentions and referral intentions. Design/methodology/approach: After conducting a survey of professional sport fans through Amazon Mechanical Turk, data were analyzed using structural equation modeling. The total sample size was 425. Findings: Results indicated the more a fan interacts with their favorite team on Facebook, the higher their relationship quality and intentions to purchase. There was no significant effect on referral intentions. Additionally, the indirect effect of Facebook interaction on purchase intention as mediated by relationship quality was positive and significant. Research limitations/implications: Based on results, it appears that relationship marketing can be used as a framework for assessing social media marketing effectiveness in sport, and that as suggested by relationship marketing theory, social media interaction does improve relationships between fans and teams. Researchers should continue to explore this model and include other variables, such as team identification, to gain a thorough understanding of social media marketing effectiveness. Practical implications: Sport marketers should focus strategy on Facebook on building relationships through content that encourages interactions between the team and fans. Originality/value: While research in sport has suggested social media be used to build relationships, little research measuring whether it actually does so exists. This study extends social media research in sport by modeling and testing the relationships between social media interaction, relationship quality and consumer behavioral intentions.